Demersal fish resources in Malaysian waters: trawl survey of trawl survey of the coastal water off the West Coast of Peninsular Malaysia (12th December 1970 - 22nd January 1971) - Mohammed Shaari Sam Abdul Latiff (Kuala Lumpur : Kementerian Pertanian dan Pembangunan Luar Bandar, 1974)
28